Socialist Realist or Republican Nationalist? Two Faces of Art Deco on Turkish Popular Magazine Covers (1930-1939) - Niyazioglu, Sinan (InfoDesign, 2019)
This paper will centre upon the visual language of the two popular Turkish youth magazines, which were designed, printed and circulated for the pre-television society of the 1930’s Turkey. New Man (Yeni Adam) and Seven Days (Yedi Gün) were the two prominent Turkish magazines of their era, as each had different political views from the other, but interestingly both had art deco visuality in common, in terms of interpreting the Modernism. Although art deco or the modern style movement was identified with new mass production industries and new consuming cultures of the 1920’s post-war European and American societies, the movement also influenced the press world of the non-industrialized and agricultural countries, located in the periphery of Europe, such as the Balkan states and Turkey. This paper aims to clarify how art deco gained different ideological features in the 1930’s Turkish mass print culture, linked with the Modernization programme of the Turkish state. New Man was a socialist realist and Seven Days was republican nationalist youth magazines, which had rich visuality and strong editorial content in common. However, each represented a different face of art deco with a different idealized ideology to liberate, to educate, to unify the masses or mainly to modernize the young society.